Clinical evidence of a graft-versus-Hodgkin's-lymphoma effect after reduced-intensity allogeneic transplantation. - Peggs, K; Hunter, A; Chopra, R; Parker, A; Mahendra, P; Milligan, D; Craddock, C; Pettengell, R; Dogan, A; Thomson, K; Morris, E; Hale, G; et al. (2005)
BACKGROUND: In patients with multiply relapsed Hodgkin's lymphoma allogeneic stem-cell transplantation has been limited by prohibitive non-relapse-related mortality rates and by a lack of definitive evidence for a therapeutic graft-versus-tumour effect. Therefore, we aimed to assess the graft-versus-tumour effect of reduced-intensity allogeneic transplantation. METHODS: We undertook reduced-intensity transplantation in 49 patients with multiply relapsed Hodgkin's lymphoma, 44 (90%) of whom had progression of disease after previous autologous transplantation (median age 32 years [range 18-51], number of previous treatment courses was five [range 3-8], and time from diagnosis 4.8 years [range 0.6-4.8]). 31 patients had HLA matched donors who were related and 18 had donors who were unrelated. Median follow-up was 967 days (range 102-2232). The primary endpoints were engraftment, toxic effects, non-relapse-related mortality, incidence of graft-versus-host disease (GVHD), and the toxic effects of adjuvant donor-lymphocyte infusion. FINDINGS: All patients engrafted. Eight of 49 (16%) had grade II-IV acute GVHD and seven (14%) had chronic GVHD before donor-lymphocyte infusion. 16 (33%) patients received donor-lymphocyte infusion from 3 months after transplantation for residual disease or progression. Six (38%) of the 16 developed grade II-IV acute GVHD and five developed chronic GVHD. Nine (56%) showed disease responses after infusion (eight complete, one partial). Non-relapse-related mortality was 16.3% at 730 days (7.2% for patients who had related donors vs 34.1% for those with unrelated donors, p=0.0206). Projected 4 year overall and progression-free survival were 55.7% and 39.0%, respectively (62.0% and 41.5% for related donors). INTERPRETATION: These data show the potential for durable responses in patients who have previously had substantial treatment for Hodgkin's lymphoma. The low non-relapse-related mortality suggests the procedure could be undertaken earlier in the course of the disease.